Crescimento e Produção da Primeira Rebrota de Cultivares de Sorgo Sob Diferentes Lâminas de Irrigação - Costa, Joao Paulo Nunes da (2017)
Sorghum is a plant indicated for the production of silage in dry regions because it presents tolerance to hydric stress and nutritional quality. Among the advantages of the culture of the sorghum it is presented the regrowth of the ratoons that allows the realization of other crops without the need to install the crop again, reducing the cost of production and the ground pressure. Due to the need to obtain information about the sorghum culture for the semi-arid region especially of new varieties, the objective of this paper is to characterize the sprout behavior of sorghum and forage sorghum cultivars in the potiguar semiarid under different irrigation slides and also to determine the irrigation blade for the sorghum crop. The experiment was carried out in the municipality of Upanema-Rn, Brazil. The trial design was a randomized complete block in a scheme of subdivided portions (4 x 5 x 2), with four replications, being four irrigation blades applied(50, 75, 100 and 125% of ETc) estimated from Kc and ETo obtained by Penman-Monteith from climate data measured in Mossoró, RN in the portion and the five cultivars (two saccharines - BRS 508, BRS 511 and three forage crops-IPA 467-4-2-B Ponta Negra) in factorial with two densities in the subplots. The spacing used was the double of 1.05 x 0.35 x 0.15 m, and the experimental plot consisted of six lines of 5 m in length. The floor area consisted of 3.0 m of the two central lines, where all the data were collected. The variables studied were: Leaf Area Index (LAI), Plant Height (m), Stem Diameter (cm) and Productivity. The data were submitted to analysis of variance (F test) and the averages were compared by the Tukey test at the 5% probability level, using the software, SAEG version 8.1. Evaluating the productivity of total fresh mass of the aerial part of resprout of five cultivars of sorghum as a function of the irrigation slides and dry mass production, it was verified that the IPA SF-15 cultivar, associated with a 100% ETc blade, along with IPA 467-4-2 and BRS Ponta Negra were more productive. The application of irrigation blade equivalent to 50% of ETc provided a reduction of only 17% of fresh biomass and 23% of dry biomass in relation to the blade (100% ETc)